Factors Affecting Broiler Breeders Following the Partnership Pattern in Gelumbang Subdistrict, Muara Enim District (An Anthropological Sociological Approach) - Acip Rakhmat; Sriati Sriati; M Yamin (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
The partnership pattern is one of the choices of business patterns faced by boiler breeders. This study aimed to describe and analyze the factors influencing the breeders to decide to follow the partnership pattern, calculate and compare the income of broiler farming business through partnership and independent patterns and analyze the perceptions of broiler breeders on the pattern to be applied to the next business cycle. The method used in this research was a survey method and stratified random sampling. The results of the study showed that the factors of venture capital, skills, result marketing and risk of loss, the marketing factor of the results were the most significant factors affecting the decision of farmers to follow the partnership pattern. It was found that the partnership pattern provided an average profit of Rp. 40,138,384.88 higher than the independent business pattern which was only Rp. 33,029,505.00 in one production period. When viewed in terms of Return Cost Ratio (R/C), livestock business through a partnership pattern was 1.19, lower than the R/C independent livestock business with a value of 1.20. Meanwhile, for the Food Conversion Ratio (FCR), both partnership and independent livestock businesses had the same value, namely 1.26. When viewed from the performance index, the livestock business through the partnership pattern had an IP of 4.25 greater in value when compared to the independent business pattern which was only 4.19. The breeders following the partnership pattern tended to decide to continue to follow the partnership pattern even though they had sufficient capital and skills, afforded to market their products independently, and faced their own risks. Keywords: breeders perception, partnership pattern, determinants of decision makers